2012
DOI: 10.1182/blood-2011-11-390807
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative differences in HTLV-I antibody responses: classification and relative risk assessment for asymptomatic carriers and ATL and HAM/TSP patients from Jamaica

Abstract: AbstractAdult T-cell leukemia (ATL) and human T-cell lymphotropic virus type I (HTLV-I)–associated myelopathy/tropical spastic paraparesis (HAM/TSP) are known to be caused by HTLV-I infection. However, current methods used to determine HTLV-I infection do not differentiate between HTLV-I asymptomatic carriers (ACs) and ATL and HAM/TSP patients. Using the luciferase immunoprecipitation system, a highly sensitive, quantitative technology that can efficiently detect HTLV-I Ab resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 46 publications
(59 reference statements)
5
35
1
1
Order By: Relevance
“…In Groups II and IV, we found that all the antibody responses against Env in the LIPS test were strong, whereas some plasma samples had much weaker responses against Gag. The detection results for Tax antibodies showed that more than half of the plasma samples in Groups II and IV tested positive with various intensities, as reported previously . Among the donors who tested positive only by CLEIA, one, seven, and eight plasma samples were positive by LIPS for antibodies against Gag, Tax, and Env, respectively, for 36 plasma samples in Group III; however, there were no positive results for the 14 plasma samples in Group V (Table ).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…In Groups II and IV, we found that all the antibody responses against Env in the LIPS test were strong, whereas some plasma samples had much weaker responses against Gag. The detection results for Tax antibodies showed that more than half of the plasma samples in Groups II and IV tested positive with various intensities, as reported previously . Among the donors who tested positive only by CLEIA, one, seven, and eight plasma samples were positive by LIPS for antibodies against Gag, Tax, and Env, respectively, for 36 plasma samples in Group III; however, there were no positive results for the 14 plasma samples in Group V (Table ).…”
Section: Resultssupporting
confidence: 81%
“…We constructed a series of plasmid vectors to express recombinant HTLV‐1 antigens, which were fused with Renilla luciferase to detect anti‐HTLV‐1 by measuring the luciferase enzyme activity levels. In previous studies that used the LIPS method to detect HTLV‐1 antibodies, the viral antigens were prepared as fusion proteins, where the Renilla luciferase protein was located at the N‐terminus of each HTLV‐1 protein . We expected that the tertiary structure of the viral protein, particularly that of the envelope glycoprotein, would be less affected by the fused luciferase protein when it was placed in the opposite order because a signal sequence that mediates targeting and translocation to endoplasmic reticulum is located at the N‐terminus of the envelope glycoprotein precursor gp62.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, infection results in an increase in proviral loads and viral expression such as Tax, Gag, and Env ( Figure 3 ). However, cells highly expressing viral proteins are eliminated by the humoral response and CTL activity of the host (Macnamara et al, 2010; Enose-Akahata et al, 2012; Enose-Akahata et al, 2013). At this stage, HBZ and APH-2 might play a crucial role by down-regulating Tax-dependent viral transcription and may allow infected cells to evade the immune response.…”
Section: Persistence Of Htlv-1 Vs Htlv-2 Infection In Relation To Thmentioning
confidence: 99%
“…However, Tax is often repressed in cells from ATLL patients (Takeda et al, 2004; Satou et al, 2006). Selective pressure mediated by strong anti-Tax immune response might justify the lack of Tax expression in ATLL cells (Hanon et al, 2000; Enose-Akahata et al, 2012). HTLV-2 is closely related to HTLV-1 and shares most viral genes such as Tax and Rex but HTLV-2 is clinically distinct from HTLV-1 since it is not associated with any forms of leukemia (Feuer and Green, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A razão pela qual aproximadamente 95% das pessoas que são infectadas pelo HTLV-1 serem assintomáticas ainda é desconhecida. A patofisiologia que ativa o estado sintomático e a razão pelo tropismo do vírus também não são completamente esclarecidas (ENOSE-AKAHATA et al, 2012;ADRY et al, 2012).…”
Section: Paraparesia Espástica Complicadaunclassified